PENGUASAAN HIRAGANA CHO ̅ON DAN YO ̅ON MAHASISWA TAHUN MASUK 2022 PRODI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - ummah, wirdatul; Zalman, Hendri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2024)
The research is motivated by student’s low mastery of hiragana chon and yon as well as difficulties in differentiating sounds in Japanese vocabulary. The aim of this research is to describe the mastery of hiragana choon and yoon of students entering the 2022 Japanese Language Education Study Program, Padang State University. Type of research used in the research this is a descriptive quantitative research. The population in this research is all students entering the 2022 Japanese Language Education Study Program, Padang State University, totaling 54 people. The sample in this research is students entering the 2022 Japanese Language Education Study Program, Padang State University, totaling 30 people. Samplin in this study used the Random Sampling technique. The data in this study were the result of the hiragana chon and yon mastery tests for students entering the 2022 Japanese Language Education Study Program, Padang State University. The instruments used in this study were multiple choice objective tests and short-fill tests. The research conducted can be concluded that the mastery of hiragana chon and yon as a whole for students entering 2022 Japanese Language Education Study Program, Padang State University’s qualifications are quite good with an average score of 68.